Indications and outcome of ventilated children in a Pediatric Intensive Care Unit of tertiary care hospital: A retrospective study - Hatti, Sachins; Uplaonkar, Vinod; Hunnalli, Charanraj (Indian Journal of Child Health, 2018)
Introduction: Mechanical ventilation (MV) is frequently used as one of the most frequent life-supportive technology in Pediatric Intensive Care Units (PICUs). Objectives: The objectives of this study are to assess the frequency, indications, and immediate outcomes in mechanically ventilated pediatric patients in the tertiary care center of developing country. Materials and Methods: A retrospective observational study was conducted among critically ill pediatric patients admitted in PICU of our institute, who required MV over the 2-year period. SPSS Software Version 22.0 was used for the statistical analysis. Quantitative data were analyzed using mean and standard deviation, and Chi-square test was used for comparing differences between categorical variables. Results: A total of 1735 patients were admitted to PICU, and 9.11% of them required MV support. The mean age in years was 1